Detention and incompatibility of HIV patients in Italy - Serena Dell'Isola; Eugenio Caturelli; Annamaria Ialungo; Elena Rastrelli; Elisabetta Liguori; Giulio Starnini (Istituto Superiore di Sanità, 2013)
In Italy, Law 231/99 and subsequent amendments standardize the conditions allowing or not a HIV positive inmate to remain in jail. Currently such clinical conditions are not automatically associated with the decline of preventive detention and the Court evaluates the incompatibility with detention on the basis of two additional and independent criteria. We have been observing the tendency by jailed HIV-positive patients to manipulate the disease state believing that the rules of incompatibility with the prison system are always applied. The management of HIV positive patients in jail involves significant sanitary and relational efforts, particularly for those suffering AIDS and/or with severe immunodeficiency.